PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM INFORMASI, REGULASI, KOMPENSASI, DAN ASAS – ASAS GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN ASET PADA BADAN USAHA MILIK DAERAH (Studi Kasus Pada Perusahaan Daerah Air Minum Kota Malang) - Tiara Prihatini; Noor Shodiq Askandar; Siti Aminah Anwar (Universitas Islam Malang, 2020)
This research was conducted to “the influence of competence of human, information system, regulation, compensation, principles of good corporate governance on the asset management in State owned enterprises. The population in this study is all of employees of the PDAM Malang city, and the samples of this study is permanent employee with bachelor degree education status with the calculation is 78 samples. The analysis method is multiple linear regression analysis with SPSS version 22 for windows software. Based on the results of simultaneous hypothesis testing shows that competence of human, information system, regulation, compensation, principles of good corporate governance affect to the asset management. Partially, the human competence, information system, regulation, and principles of good corporate governance affect asset management but the compensation its can not affect to the asset management off company. Keywords: Human Competence, Information System, Regulation, Compensation, Principles of Good Corporate Governance, and Asset Management